FORMULATION AND PHYSICAL STABILITY TESTING OF CREAM SCRUB PREPARATIONS FROM ETHANOL EXTRACT OF Nelumbo nucifera GAERTN FLOWER AND LEAF - Khairani Fitri; Tetty Noverita Khairani; Muhammad Andry; Muhammad Amin Nasution; Muhammad Fauzan Lubis; Firman Rezaldi; Jashima Ukhtia (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2024)
Nelumbo nucifera is an aquatic plant that thrives in muddy and soggy soil, particularly in swampy environments. Nelumbo nucifera is utilized in traditional medicine for various purposes, including the management of diarrhea, tissue inflammation, and homeostasis. The flowers and leaves of Nelumbo nucifera contain many secondary metabolite chemicals, including flavonoids, alkaloids, tannins, and antioxidants. The objective of this study is to ascertain the feasibility of formulating a cream scrub using the ethanol extract of Nelumbo nucifera flowers and leaves. Additionally, the study attempts to discover if concentrations of 3%, 5%, and 7% of this extract can effectively moisturize the skin. This research technique is based on experimentation, involving the creation of simplicia, the production of extracts, the formulation of body scrub preparations using ethanol extracts of Nelumbo nucifera flowers and leaves, and the subsequent evaluation of these body scrub preparations. This study found that the moisture content of Nelumbo nucifera flower ethanol extract cream increased by 41.2% in F1, 46.5% in F2, and 52.9% in F3. The humidity percentage values for Nelumbo nucifera leaf extract cream were obtained as follows: F1 at 38.8%, F2 at 44.4%, and F3 at 47.7%. The ethanol extract derived from the flowers and leaves of Nelumbo nucifera can be prepared and used as a cream scrub. A cream scrub containing Nelumbo nucifera flower and leaf extract at concentrations of 3%, 5%, and 7% can effectively moisturize the skin.